Tantangan dan Peluang dalam Dinamika Komunikasi Penyiaran Islam dalam Era Digital - Hendra Lesmana (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2025)
In the era of continuously developing digital technology, the dynamics of Islamic broadcasting communication are experiencing a significant transformation. This research uses a qualitative approach which aims to explore the challenges and opportunities faced by Islamic broadcast communications in the midst of the digital revolution. The research results show that rapid changes in information technology and digital media have an impact on the way Islamic messages are spread and received by society. Apart from that, these changes also have an impact on Islamic broadcasting methods related to the effectiveness of messages in reaching an increasingly digitally connected audience. There are a number of key challenges involving the expansion of social media, the rapid dissemination of information and the diversity of digital platforms.